Ionotropic Gelation-Based Synthesis of Chitosan-Metal Hybrid Nanoparticles Showing Combined Antimicrobial and Tissue Regenerative Activities - Laura Lozano Chamizo (MDPI AG, 2021)
The treatment of skin wounds poses significant clinical challenges, including the risk of bacterial infection. In particular due to its antimicrobial and tissue regeneration abilities chitosan (a polymeric biomaterial obtained by the deacetylation of chitin) has received extensive attention for its effectiveness in promoting skin wound repair. On the other hand, due to their intrinsic characteristics, metal nanoparticles (e.g., silver (Ag), gold (Au) or iron oxide (Fe3O4)) have demonstrated therapeutic properties potentially useful in the field of skin care. Therefore, the combination of these two promising materials (chitosan plus metal oxide NPs) could permit the achievement of a promising nanohybrid with enhanced properties that could be applied in advanced skin treatment. In this work, we have optimized the synthesis protocol of chitosan/metal hybrid nanoparticles by means of a straightforward synthetic method, ionotropic gelation, which presents a wide set of advantages. The synthesized hybrid NPs have undergone to a full physicochemical characterization. After that, the in vitro antibacterial and tissue regenerative activities of the achieved hybrids have been assessed in comparison to their individual constituent. As result, we have demonstrated the synergistic antibacterial plus the tissue regeneration enhancement of these nanohybrids as a consequence of the fusion between chitosan and metallic nanoparticles, especially in the case of chitosan/Fe3O4 hybrid nanoparticles.